Lack of interest from students towards school as a result of the post-pandemic educational phenomenon: approach from a systematic review - Nápoles Nápoles, Karen (Revista Ecos de la Academia, 2023)
The Covid-19 pandemic changed the obligation to adopt a new educational modality never before experienced by many, virtual education being a test and experimentation scenario that, in addition to further deepening the educational gap in Mexico and many other Latin American countries, evidenced another even more severe problem, the discouragement of learning, along with the demotivation of students to maintain an active participation in their academic tasks, an essential element that the new educational modality demanded. The bibliography suggests how the affectation to the emotional, affective and mental well-being of the students strongly diminished the phenomenon of school demotivation. This work being an approximation to a systematic review that, through the analysis of fifty documents consulted in different digital repositories such as Redalyc, Dialnet and Google Académico, responds to the research assumptions raised and the defined objectives, one of them being to analyze the various factors that influence the school demotivation of students as a result of virtual education. This review made it possible to find that current scenarios demand students capable of showing a certain tolerance to frustration to adapt to these transformations, without weakening the pursuit of their academic objectives.